The Effectiveness of the Talkpal AI-Based Project-Based Learning (PjBL) Model in Enhancing Arabic Speaking Skills: Efektivitas Model Project-Based Learning (PjBL) Berbasis AI Talkpal dalam Meningkatkan Keterampilan Berbicara Bahasa Arab - Haniefa, Rifda; Ch, Hendrawanto; Nafi’ah, Khotimatun (ELOQUENCE : Journal of Foreign Language, 2025)
Background: Mastering speaking skills demands more than just theoretical knowledge; it also requires real-world application to foster meaningful and practical learning. In the Arabic Language Education Program at the Faculty of Language and Arts, Universitas Negeri Jakarta (UNJ), the curriculum is structured to develop both theoretical understanding and practical proficiency in language use. However, the researcher observed that students often struggle with Arabic speaking performance, particularly in areas such as pronunciation, fluency, vocabulary usage, and maintaining coherent content. Objective: The purpose of this study is to evaluate the effectiveness of integrating the Talkpal AI-based Project-Based Learning (PjBL) approach in enhancing Arabic speaking skills. Method: This research adopts a pre-experimental design involving a single group with pre-test and post-test stages. Data collection methods included oral examinations, observations, and interviews. Participants were selected through purposive sampling, comprising 25 second-semester students from class F of the Arabic Language Education Program. The quantitative data gathered were processed and analyzed using SPSS version 24. Results and Discussion: Findings from the paired sample t-test indicate a significant improvement, with a sig. (2-tailed) value of 0.00, which is below the 0.05 threshold thus, the null hypothesis is rejected in favor of the alternative. This outcome aligns with the N-Gain analysis, which revealed an average score of 82.0326. According to the criteria (g > 0.7), this result falls into the high and effective category, also consistent with Malzer’s classification. Conclusion and Implications: Based on the statistical analyses conducted, it is evident that the implementation of the Talkpal AI-based PjBL model significantly enhances students’ Arabic speaking abilities. The results suggest that embedding AI-powered tools within project-based instructional strategies can serve as an effective and adaptable means of fostering language skill development in the context of digital-age education.